Gone with the wand : a fairy's tale - Palatini, Margie; Ajhar, Brian (New York : Orchard Books, 2009)
When tooth fairy Edith B. Cuspid finds her friend Bernice Sparklestein, a fairy godmother whose work is legendary, having a very bad wand day, she tries to cheer her up by suggesting Bernice try other fairy jobs.
Kirkus Review.
3.6
K-3
Keywords: Fairies -- Juvenile fiction; Fairy godmothers -- Juvenile fiction; Magic -- Juvenile fiction; Occupations -- Juvenile fiction; Tooth Fairy (Legendary character) -- Juvenile fiction; Fairies -- Fiction; Fairy godmothers -- Fiction; Magic -- Fiction; Occupations -- Fiction; Tooth Fairy -- Fiction; Fairies -- Fiction; Fairy godmothers -- Fiction; Magic -- Fiction; Occupations -- Fiction; Tooth Fairy -- Fiction